ARIF WELDI FERDIAN STUDI KONDISI FISIK ATLET SEPAKBOLA DI PUSAT PENDIDIKAN DAN LATIHAN OLAHRAGA PELAJAR (PPLP) SUMATERA BARAT - Arif Weldi Ferdian, Arif; Hastria Effendi; Hadi Pery Fajri; Didin Tohidin (Jurnal IKEOR, 2023)
Abstract Football at the West Sumatra Student Sports Education and Training Center (PPLP). Many factors cause. For this reason, it is necessary to conduct a study with the aim of reviewing the physical condition of football athletes at the West Sumatra Student Sports Education and Training Center (PPLP). This type of research is descriptive, this research was conducted in February 2023. The population in the study were all football athletes at the West Sumatra Student Sports Education and Training Center (PPLP), totaling 20 people. Samples were taken from all players totaling 20 people by means of total sampling. Data collection used a test, with the following instruments: 1) Yoyo Test to measure aerobic endurance, 2) Run 30 Meters to measure speed, 3) Illinois Agility to measure agility. The analysis technique used is the frequency distribution technique. The results of research on the level of physical condition of football athletes at the West Sumatra Student Sports Education and Training Center (PPLP) show that: 1) The average athlete’s aerobic endurance is 42.45 which is categorized as moderate. 2) The average athlete’s speed is 4.77 secs which is categorized as moderate. 3) The average athlete’s agility is 17.27 secs which is categorized as moderate. Keywords: Physical condition , Football , PPLP west sumatra